Effects of a carbohydrate‐restricted diet on hepatic lipid content in adolescents with non‐alcoholic fatty liver disease: A pilot, randomized trial. Issue 7 (4th March 2020) - Goss, Amy M.; Dowla, Shima; Pendergrass, May; Ashraf, Ambika; Bolding, Mark; Morrison, Shannon; Amerson, Alesha; Soleymani, Taraneh; Gower, Barbara
Summary: Background: Non‐alcoholic fatty liver disease (NAFLD) has emerged as the most common form of liver disease among adolescents in industrialized countries. While lifestyle intervention remains the hallmark treatment for NAFLD, the most effective dietary strategy to reverse NAFLD in children is unknown. Objective: The objective of this study was to determine the effects of a moderately CHO‐restricted diet (CRD) vs fat‐restricted diet (FRD) in adolescents with NAFLD on reduction in liver fat and insulin resistance. Methods: Thirty‐two children/adolescents (age 9‐17) with obesity and NAFLD were randomized to a CRD (<25:25:>50% energy from CHO:protein:fat) or FRD (55:25:20) for 8 weeks. Caloric intakes were calculated to be weight maintaining. Change in hepatic lipid content was measured via magnetic resonance imaging, body composition via dual energy X ray absorptiometry and insulin resistance via a fasting blood sample. Results: Change in hepatic lipid did not differ with diet, but declined significantly (−6.0 ± 4.7%, P < .001 only within the CRD group. We found significantly greater decreases in insulin resistance (HOMA‐IR, <.05), abdominal fat mass ( P < .01) and body fat mass ( P < .01) in response to the CRD vs FRD. Conclusion: These findings suggest that consumption of a moderately CHO‐restricted diet may result in decreased hepatic lipid as well as improvements in body composition and insulin resistance in adolescents with NAFLD even in the absence of intentional caloric restriction. Larger studies are needed to determine whether a CHO‐restricted diet induces change in hepatic lipid independent of change in body fat.